THE IMPORTANCE OF FILM THICKNESS ON THE PHOTOVOLTAIC PERFORMANCE OF PEROVSKITE SOLAR CELLS - Sanni, Dahiru M.; Joseph, Emmanuel; Adamu, Muhammad Aminu (FUDMA JOURNAL OF SCIENCES, 2020)
In this study, we investigated the role of film thickness on the photovoltaic performance of perovskite solar cells (PSCs) fabricated from dehydrated lead acetate as the source material. The inverted p-i-n planar heterojunction architecture was adopted in this work. One step spin-coating methods were used in depositing the perovskite solution before annealing on a hot plate at 90 oC for 5 minutes to form the perovskite film. We varied the film thickness by varying the spin-coating rate from 2000 to 6000 rpm for 60 seconds and the optimal film thickness was obtained at 4000 rpm corresponding to 400 nm. This gave the best power conversion efficiency (PCE) of 11.61%, Open circuit voltage (Voc) of 0.909 V, short circuit photocurrent density (Jsc) of 20.41 mA/cm2 and fill factor (FF) of 62.56%. Our investigations revealed that film thickness has great influence in the photovoltaic performance of PSCs.